(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The current study aims to compare and analyze workplace morale among primary school teachers in public and private sectors in the public and private sectors in Himachal Pradesh. Himachal Pradesh is recognized as one of the most literate and educationally developed states in India. Teacher morale includes job satisfaction, motivation, and emotional health, and is ultimately important for effective instruction and the continuing success of a school. Public and private sectors differ in institutional support, salary structures, workloads, and opportunities for advancement which can lead to disparate morale among teachers. Using a mixed-methods design where quantitative and qualitative dimensions are used to better understand the differences, the quantitative part consists of a morale scale which the researcher administered to a sample of 240 teachers in public and private primary schools in selected districts of Himachal Pradesh, while the qualitative part consists of semi-structured interviews with some of the respondents focusing on the factors that shape their morale and professional experiences. Quantitative data will be further analyzed using descriptive statistics, t-tests, and regression while qualitative data will be analyzed using thematic analysis. The study attempts to describe key workplace morale predictors and provide sector-specific explanations along with evidence-based recommendations to improve teacher morale and motivation. This information should help policymakers, school administrators, and educational planners understand how to improve teacher morale and, as a result, improve the educational standards and learning outcomes for primary education in Himachal Pradesh.